VOCABULARY MASTERY THROUGH TEACHER-LED ACTIVITIES USING MISSING WORDS FOR THE TENTH GRADE STUDENTS - Febriyanti; Sri Wahyuningsih; Dian Cahya Novalia (English Department, STKIP PGRI Bandar Lampung, 2021)
The study aimes to know wheter there is positive influence of teacher-led activities using missing words towards students’ vocabulary matery at the senior high school level. In this research the writer used an quasi experimental method. It consisted of two classes: they are experimental class and control class. The population of this research was the students at the second semester of the tenth grade at MAN 1 Pesawaran. The population consisted 251 students from six classes. The sample of the research was X1 and X2. Then for sampling technique the writer used Random Sampling technique. To collect the data, the writer used multipe choice test and to prove hypothesis, the writer used t-test formula. After analyzing the data, the writer tested the hyphotesis and the result of tratio= 5,61, ttable= 1,98 for α = 0,05 It means that tratio> ttable. It means that there is significant influence of teacher-led activities using missing words toward students’ vocabulary mastery at the second semester of the tenth grade at MAN 1 Pesawaran